Performance of fungicides on the control of fusarium head blight (Triticum aestivum L.) and deoxynivalenol contamination in wheat grains - Bonfada,Éverson Bilibio (2019)
ABSTRACT Fusarium head blight (FHB) is considered a disease of difficult control in a scenery of obstacles for its chemical control and due to the aggressiveness of its pathogen in producing toxins. Thus, the objective of this study was to verify if fungicides of different chemical groups, alone or in combination, are effective in controlling fusarium head blight and reducing deoxynivalenol (DON) contamination in wheat grains. In addition, pyraclostrobin alone was evaluated for possible changes on fusarium head blight intensity and DON accumulation reflecting on the yield. The experiments were conducted in the field, in a randomized block design, containing 11 treatments and four replicates, using the cultivar TBIO Toruk. The treatments were composed of the fungicides triazole, strobilurin and benzimidazole alone, besides the commercial mixture of triazole + strobilurin. Two fungicide applications were performed during the crop flowering. Fusarium head blight intensity, control efficacy, DON contamination and grain yield were evaluated. Data were subjected to analysis of variance (F-Test at 5%) and means were compared according to Scott-Knott test, at 5%. Carbendazim alone presented greater control efficacy in the two studied years (67% and 75%, respectively), differing from metconazole and pyraclostrobin. Pyraclostrobin at different doses and application stages changed fusarium head blight intensity, DON contamination and wheat grain yield.